Internal And External Factors That Affect Village Government Performance - Anisah, Helmi Nur; Falikhatun, Falikhatun (Universitas Pendidikan Indonesia, 2021)
This study aims to examine the effect of Regulation, Organizational Commitment, Human Resources Quality, Internal Control Systems, Participation in Budgeting, and Utilization of Information Technology on Village Government Performance. The population in this study is all village apparatus in Klego Sub-District, Boyolali District, while the samples were selected using the convenience sampling method. The data collection process collected responses from 49 respondents that consist of Village Chief, Village Secretary, Head of Section, and Village Financial System (Siskeudes) Operator. The analysis results concluded that Regulation, Participation in Budgeting, and Utilization of Information Technology have a positive effect on Village Government Performance, while Organizational Commitment, Human Resource Quality, and Internal Control System do not affect Village Government Performance. The finding of this study needs to be a concern for an auditor because the variables that affect Village Government Performance might provide an opportunity for fraud to take place in the Village Budget management.